Research Article Genetic Association of AGT rs699 with Hypertension in a Population from Rawalpindi, Pakistan - Mumtaz, Fazila; Maqbool, Ayesha; Ali, Akhtar; Kiyani , Mubin Mustafa; Ali, Yasir (BioScientific Review, 2026)
Background. Hypertension is a widespread chronic illness, and ranks as one of the leading causes of death. Some complications of having chronic hypertension include cardiovascular diseases (CVDs), strokes, and chronic renal diseases. Evidence from epidemiological studies represent that hereditary factors and genes are involved in the etiology of hypertension. Therefore, the current study aimed to discuss the association of rs699 point mutation of AGT gene, which results in the M268T substitution (Methionine>Threonine). The objective of this study was to investigate the association of hypertension with the SNP rs699 of AGT gene. Methods. A total of 80 participants were included in this case-control study, with 50 hypertension patients and 30 controls. The blood samples were collected from multiple hospitals in Rawalpindi district. The genomic DNA was isolated. Amplification Refractory Mutation System-Polymerase Chain Reaction (ARMS-PCR) method was used to find allele frequencies. Results. Genotypic analysis indicated a strong association of T allele of rs699 with hypertension. For T allele, both heterozygotes and homozygotes were found to have an elevated risk of hypertension. The study found that the odds ratio of TT genotype was 3.5 times higher for patients than those who had the CC genotype (OR=3.5), 95% Confidence Interval (CI) indicating a higher risk of hypertension. Whereas, the odds of disease in individuals with the "CT" genotype were lower than those with the "CC" genotype (OR=0.5), 95% CI." Conclusion. These findings demonstrated that rs699 polymorphism of AGT gene is significantly associated with the susceptibility to hypertension.